Optimal C1, α regularity for degenerate fully nonlinear elliptic equations with Neumann boundary condition. (September 2020) - Ricarte, Gleydson C.
Abstract: In the present paper, we study sharp C 1, α regularity results with boundary Neumann condition for viscosity solutions for a class of degenerate fully non-linear elliptic equations.